Orange Chromide, Pseudetroplus maculatus (Bloch., 1795): A Potential Euryhaline Fish Model to Evaluate Climate Change Adaptations in Fishes - Padinhate Purayil, Suresh Babu; Thomas, Shilta M.; Anirudhan, Anuraj; Sidhick, Jeena Nikarthil; Kandiyil, Asokan Pillaru; Ebeneezar, Sanal; Ignatius, Boby; Achamveetil, Gopalakrishnan (Frontiers in Marine Science, 2022)
Orange chromide, Pseudetroplus maculatus is a euryhaline species with both ornamental and food value. The species has several attributes similar to other fish model organisms such as smaller size, repeated breeding, ease of maintenance, and higher fecundity. A salinity tolerance study was performed in different salinities (0, 15, and 35 ppt) in triplicate introducing 10 fishes each (5.4 ± 0.08 g) in 12 plastic tanks of 60 L water-holding capacity. Fish were fed with commercial feed (1.2 mm and 40% protein) at 5% of body weight twice daily for 45 days. No significant variation (p< 0.05) in growth and survival was observed during the study indicating the wide salinity tolerance for the species. Experimental breeding of the species in freshwater and seawater (35 ppt) revealed the ability of the species to breed in varying salinities. Lenience in captive broodstock development, pair formation, and year-round natural breeding makes the seed production of the species easier. Characteristics such as multiple spawnings, a prolonged incubation period (48 to 72 hours) useful for elaborative embryonic studies, shorter larval development cycle (25 to 30 days), and better acceptance of live feed (Artemia nauplii and flakes) and commercial feed by the larvae make the species a potential euryhaline ornamental fish model to assess the physiological changes at different salinities. Minimal input requirements and lower capital and operational investments for the seed production of the species make it an ideal model organism for studying the impact of climatic and environmental changes on fish farming in different habitats.